Adsorption of methylene blue using activated carbon from mixed of palm oil press fibres and empty fruit bunch - Amir Rahimie, Ridzuan (2012)
Nowadays,palm oil industry wastes such as palm oil empty fruit bunch and palm oil press fibre have been sold as source of energy renewable in Malaysia.In the combustion process of palm oil empty fruit bunch and palm oil press fibre will produce carbon.This carbon can be activated to use in waste water treatment and chemical absorber. Methylene blue was use as adsorbate with different concentration.The activated carbons have been produce using chemical activation using potassium hydroxide.It has been carbonize at 250oC for 24 hour with nitrogen flow and the activation process also as carbonize process with temperature 300oC.The equilibrium study using UV-Visible Spectrophotometer is to make calibration curve and to determine the final concentration of the methylene blue solution.From the experiment,the adsorption graph show the 50% additional percentage weight of empty fruit bunch into palm oil press fibres give the high adsorption percentage and from the lagmuir isotherm it also give the high value R2 and it maximum adsorption capacity is 111.111 mg/g.The characterization of the activated carbon produce have been determine using Fourier Transform Infrared Spectroscopy (FTIR),it presence of –OH (hydroxyl),C-H (alkanes and alkyls),C=O (Ketone or Asidcarbosilik),and C-O-C(esters, eter or phenol)From this research,that can conclude the activated carbon is successfully produce and the characterization of the activated carbon also determine using FTIR.The optima condition is at 50% additional percentage weight of empty fruit bunch into palm oil press fibre.